2009
DOI: 10.1245/s10434-009-0673-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategy of Papillary Thyroid Carcinoma in Children and Adolescents: Clinical Significance of the Initial Nodal Manifestation

Abstract: Initial nodal manifestation is useful to predict DFS in younger papillary thyroid carcinoma patients. Our findings will be beneficial to determine the treatment strategy. Conservative therapy is considered acceptable for patients without risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 38 publications
2
42
0
1
Order By: Relevance
“…Total or near total thyroidectomy and central lymph node dissection were performed in all patients after rapid frozen section confirmation of thyroid carcinoma. In a series reported by Enomoto et al [25] total thyroidectomy was performed in 8%, by Wada et al [41] in 25%, by Hay et al [13] in 38% and by Ito et al [40] in 54% of patients. The extent of surgery on central and lateral lymph nodes also varies among series.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Total or near total thyroidectomy and central lymph node dissection were performed in all patients after rapid frozen section confirmation of thyroid carcinoma. In a series reported by Enomoto et al [25] total thyroidectomy was performed in 8%, by Wada et al [41] in 25%, by Hay et al [13] in 38% and by Ito et al [40] in 54% of patients. The extent of surgery on central and lateral lymph nodes also varies among series.…”
Section: Discussionmentioning
confidence: 96%
“…Surgery of thyroid carcinoma in children varies among institutions regarding the surgery on thyroid gland and the lymph nodes. Many authors prefer procedures less than total thyroidectomy [13,25,40,41]. Our surgical strategy is similar to the management of adult differentiated thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…These lesions are osteolytic on skull X-ray and CT scan and highly vascular on angiographic assessment [1,17] . Prognosis in the case of metastasis is generally poor and the 10-year survival with bone metastasis from differentiated thyroid cancers is reported to be 27% [2] . Since the presence of bone metastasis markedly worsens the prognosis, early detection is important.…”
Section: Discussionmentioning
confidence: 99%
“…Papillary carcinoma may be considered a variant of mixed form thyroid carcinoma. Despite its well-differentiated characteristics, papillary carcinoma may be overtly or minimally invasive [2] . In fact, these tumors may spread easily to other organs.…”
Section: Introductionmentioning
confidence: 99%
“…(Figure 4) Multiple studies have shown that ultrasound allows the surgeon to plan for extent of thyroidectomy (Mazzaglia, 2010;Papini, 2002;Park et al, 2009;Stulak et al, 2006). The authors (M.G and J.I.L) believe that ultrasound should be used routinely in the evaluation of thyroid nodules in pediatric patients with reports in the literature suggesting its advantage for this specific purpose Stulak et al, 2006;Wada et al, 2009). …”
Section: Neck Ultrasoundmentioning
confidence: 99%